Highly efficient and robust catalysts for the hydrogen evolution reaction by surface nano engineering of metallic glass. Issue 9 (12th January 2021) - Yan, Yuqiang; Wang, Chao; Huang, Zhiyuan; Fu, Jianan; Lin, Zezhou; Zhang, Xi; Ma, Jiang; Shen, Jun
Abstract : The synthesized hybrid electrocatalyst has excellent efficiency and stability for the HER. Abstract : Efficiency and stability are the key parameters for the hydrogen evolution reaction (HER) of water electrolysis, and therefore developing effective and robust catalysts has been a long standing pursuit. In this work, we propose a flexible and universal strategy to synthesize catalysts with excellent HER catalytic performance. Following this strategy, we successfully fabricate a hybrid electrocatalyst by decorating Pt particles on a nano engineered metallic glass (MG) surface (Pt@MG NWs). The overpotential of the catalyst to achieve a geometric current density of 10 mA cm −2 is 48.5 mV in 0.5 M H2 SO4 . Astonishingly, the Tafel slope is only 19.8 mV dec −1, smaller than that of commercial 10% Pt/C. The Pt@MG NWs exhibit excellent charge transport efficiency and contain around 3 times more active sites than 10% Pt/C. In addition, the Pt@MG NWs are ultra-stable, exhibiting no degradation after the HER at overpotentials of 48.5 mV and 84 mV for 20 hours. Furthermore, this catalyst shows enhanced catalytic performance when a large working current is applied at an overpotential of 200 mV for 500 hours. The hydrophilicity and aerophobicity of Pt@MG NWs, which originate from surface structural construction, are responsible for the outstanding HER catalytic performance. The calculations found that the hybrid electrocatalyst exhibits small Gibbs free energy and strong H2 O adsorption energy. Our results provide a novel and universal approach for designing superior HER catalysts with excellent activity and stability.